Utilizing animal manure-derived biochar in catalytic advanced oxidation processes: A review - Yang, Heejin; Lee, Chang Gu; Lee, Jechan (Journal of Water Process Engineering, 2023)
Over the past decade, the accumulation of animal manure has noticeably increased, raising concerns regarding proper disposal methods. Therefore, the use of animal manure for biochar production has gained increasing attention, with biochar emerging as a carbon-rich resource. Biochar derived from manure exhibits distinctive attributes, including an expansive surface area and elevated carbon content, rendering it a potential catalyst for catalytic advanced oxidation processes (AOPs), namely persulfate activation, Fenton-like process, photocatalysis, and ozonation. The properties, catalytic performance, and functional roles of animal manure-derived biochars, especially the catalytic potential within the activation process, were analyzed and organized. The performance of catalytic AOPs in pollutant removal is influenced by factors, such as the catalyst dose, oxidant concentration, pH, and temperature, with varying importance depending on the process. The catalytic performance of animal manure-derived biochars originates from the unique properties that make them effective catalysts. These biochars have high carbon and nitrogen contents, creating active sites that play a crucial role in catalytic AOPs. In addition, diverse functional groups are formed during pyrolysis, and metals and phenolic compounds in the biomass interact with oxidants to generate reactive oxidative species (ROS). In catalytic AOPs using animal manure-derived biochars, ROS are generated via two pathways: radical formation and non-radical mechanisms, which produce species, such as OH[rad], SO4[rad]−, O2[rad]−, and 1O2. This study demonstrates the role of animal manure-derived biochars in catalytic AOPs and supports their use. These biochars are consistent with several sustainable development goals, including those related to water, energy, responsible consumption, climate, and biodiversity. Overall, biochar derived from animal manure has the potential for sustainable development and environmental protection.
Keywords: Excretion-based biochar; Heterogeneous catalyst; Organic pollutants; Reactive oxidation species